2006
DOI: 10.1111/j.1600-0471.2006.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

The mineral wealth of ancient Arabia and its use I: Copper mining and smelting at Feinan and Timna – comparison and evaluation of techniques, production, and strategies

Abstract: Near Eastern fieldwork in mining archaeology and archaeometallurgy began at Timna (Israel) in the 1960s and 1970s and continued in Feinan (Jordan) in the 1980s and 1990s. For the first time, Bronze Age copper mines were excavated and cleared and importance was given to the slag recovered. At both sites copper was produced for over 5000 years, from the Chalcolithic to the Mamluk periods. Although the broad outlines of technical development can be traced, much remains to be learned in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The signature can be traced to a single vast ore district covering both sides of the Araba rift valley between the Dead Sea and the Red Sea, with Faynan on the eastern side and Timna on the western. Both districts have been extensively mined in antiquity, and at Faynan copper has been produced on an industrial scale as early as the middle of the third millennium BC (Weisgerber 2006; for a detailed discussion and a comprehensive bibliography see Hauptmann 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The signature can be traced to a single vast ore district covering both sides of the Araba rift valley between the Dead Sea and the Red Sea, with Faynan on the eastern side and Timna on the western. Both districts have been extensively mined in antiquity, and at Faynan copper has been produced on an industrial scale as early as the middle of the third millennium BC (Weisgerber 2006; for a detailed discussion and a comprehensive bibliography see Hauptmann 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A long-term research programme by the BochumJordanian Archaeometallurgical Research Group (Hauptmann, 1989(Hauptmann, , 1997(Hauptmann, , 1990(Hauptmann, , 1992(Hauptmann, , 2000Weisgerber, 1987, 1992;Najjar et al, 1990Najjar et al, , 1995Nikliewski and van Zeist, 1970) detected a w9000 year history of the exploitation of copper ores at and around the Khirbet Faynan. A programme of research by the University of California, San Diego and the Jordanian Department of Antiquities addressed the social archaeology in a deep-time study of the role of mining and metallurgy on the evolution of societies in the southern Levant, with detailed archaeological surveys and large-scale excavations (Higham et al, 2005;Levy, 2004Levy, , 2006Levy et al, 2003Levy et al, , 2004aLevy et al, ,b,c, 2002Levy et al, , 1999aLevy et al, ,b, 2001aLevy et al, ,b, 2005aLevy and Higham, 2005a,b;Levy and Najjar, 2005a,b;Muniz, 2006;Weisgerber, 2006). After relatively small-scale and local gathering of copper and copper ores in the Neolithic, and ''household pyrotechnology'' in the Early Bronze Age, copper production became intense in the Wadi Faynan area and down-Wadi in the vicinity of Wadi Fidan (Adams, 2002;Lewin et al, 1977Lewin et al, , 1995Grattan et al, 2007).…”
Section: Mining and Smelting Of Copper Oresmentioning
confidence: 96%
“…Weeks et al (2009) suggested three main copper sources within and around Arabia which were exploited since before the Iron Age. Geographically, the most likely copper source for Tayma and Qurayyah would be the Jordan rift valley of northwest Arabia with the famous ancient mining and smelting sites at Feinan and Timna (Rothenberg, 1972;Hauptmann, 2007;Weisgerber, 2006). The second major potential copper source for these two sites is in current Oman and the northern United Arab Emirates where copper was exploited as early as the second half of the third millennium BC and at least until the pre-Islamic period (Weeks, 2003).…”
Section: Lead Isotope Analysismentioning
confidence: 99%